MODEL PENGATURAN YANG EFEKTIF TERKAIT PENGELOLAAN PASAR TRADISIONAL DI INDONESIA - Sudi Fahmi; Ardiansah; DONI APRIALDI (Fakultas Hukum, Universitas Samudra, 2021)
Abstract, This study aims to discuss the existence of the regulation of the Minister of Trade No. 56/M.DAG/PER/9/2014 and analyze the implementation problems. This research is normative legal research (juridical normative) using a statutory approach and a conceptual approach where the analysis method is carried out qualitatively. The results of the study indicate that the state must promote Indonesian national culture, one of which is to maintain and maintain traditional markets in Indonesia as a manifestation of cultural identity and one of Indonesia's national cultures. This is enshrined in the constitution based on Article 32 paragraph (1) of the 1945 Constitution of the Republic of Indonesia. About the arrangement of traditional markets in Indonesia, specific and detailed arrangements relating to traditional markets are regulated by Presidential Regulation Number 112 of 2007 concerning Arrangement and Development of Traditional Markets, Shopping Centers, and Modern Stores was then followed up with Minister of Trade Regulation Number 70/MDAG/PER/12/2013 concerning Guidelines for Arrangement and Development of Traditional Markets, which was later updated with Minister of Trade Regulation No: 56/M/DAG /9 2014 the Year 2014. However, the Minister of Trade Regulation only regulates the arrangement of modern markets. The existence of people's markets or traditional markets which are in great demand by the community to this day still causes polemics in their management, so they are often considered not so necessary. Therefore, it is very important to pay attention to the interests of the community from all levels, especially government policies in the regulation and management of emerging markets. Because the Indonesian constitution has explained that the state is responsible for providing protection and is responsible for maintaining traditional markets in Indonesia. Keywords: Arrangement, Regulation, and Management, People's Markets or Traditional Markets Abstrak. Penelitian ini bertujuan untuk membahas eksistensi dari peraturan Menteri Perdagangan Nomor. 56/M.DAG/PER/9/2014 dan menganalisis problematika pelaksanaannya. Penelitian ini merupakan penelitian hukum normatif (yuridis normatif) dengan menggunakan pendekatan perundang-undangan (statute approach) dan pendekatan konsep (conceptual approach) dimana metode analisis dilakukan secara kualitatif. Hasil penelitian menunjukkan bahwa negara mempunyai kewajiban untuk memajukan kebudayaan nasional Indonesia salah satunya adalah dengan tetap menjaga dan mempertahankan pasar-pasar tradisional di Indonesia sebagai wujud dari identitas budaya dan salah satu kebudayaan nasional Indonesia. Hal ini termaktub didalam konstitusi berdasarkan Pasal 32 ayat (1) Undang-undang Dasar Republik Indonesia tahun 1945. Berkaitan dengan penataan pasar-pasar tradisional di Indonesia, pengaturan secara khusus dan terperinci yang berkaitan dengan pasar tradisional diatur dengan Peraturan Presiden Nomor 112 Tahun 2007 tentang Penataan dan Pembinaan Pasar Tradisional, Pusat Perbelanjaan, dan Toko Modern kemudian ditindaklanjuti dengan Peraturan Menteri Perdagangan Nomor 70/MDAG/PER/12/2013 tentang Pedoman Penataan dan Pembinaan Pasar Tradisional, yang kemudian diperbaharui dengan peraturan Menteri Perdagangan No: 56/M/DAG/9 2014 Tahun 2014. Namun Permendag tersebut hanya mengatur terkait penataan pasar modern saja. Keberadaan pasar rakyat atau pasar tradisional yang banyak diminati oleh masyarakat sampai hari ini masih menimbullkan polemik dalam pengelolaannya, sehingga sering kali dianggap tidak begitu diperlukan. Oleh karena itu, kepentingan masyarakat dari segala tingkatan sangat perlu diperhatikan terutama kebijakan pemerintah didalm pengaturan dan pengelolaan pasar-pasar yang bermunculan. Karena konstitusi Indonesia telah menjelaskan bahwa negara bertanggung jawab untuk memberikan perlindungan dan bertanggung jawab mempertahankan pasar-pasar tradisional di Indonesia. Kata Kunci: Penataan, Pengaturan dan Pengelolaan, Pasar Rakyat atau Pasar Tradisional